2016
DOI: 10.18632/oncotarget.9473
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of history of follicular lymphoma, induction regimen and stem cell transplant in patients withMYC/BCL2double hit lymphoma

Abstract: MYC/BCL2 double hit lymphoma (DHL) has been the subject of many studies; however, no study has systemically compared the clinicopathologic features and prognostic factors between patients with de novo disease versus those with a history of follicular lymphoma (FL). In addition, the prognostic importance of several other issues remains controversial in these patients. In this retrospective study, we assess 157 patients with MYC/BCL2 DHL including 108 patients with de novo disease and 49 patients with a history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 37 publications
(46 reference statements)
2
36
0
Order By: Relevance
“…All the cases were diagnosed as either diffuse large Bcell lymphoma or B-cell lymphoma, unclassifiable, with features intermediate between diffuse large B-cell lymphoma and Burkitt lymphoma based on their morphological features and all cases were classified as high-grade B-cell lymphoma with MYC, BCL2, and BCL6 rearrangements based on the current WHO classification. The study group was further compared to 157 cases of MYC/BCL2 double hit lymphoma and 13 cases of MYC/BCL6 double hit lymphoma that have been reported previously [18,19,21] ( Table S1). The overall survival (overall survival) of patients with triple hit lymphoma was also further compared with a group (n = 467) of patients with diffuse large B-cell lymphoma without MYC rearrangement.…”
Section: Case Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the cases were diagnosed as either diffuse large Bcell lymphoma or B-cell lymphoma, unclassifiable, with features intermediate between diffuse large B-cell lymphoma and Burkitt lymphoma based on their morphological features and all cases were classified as high-grade B-cell lymphoma with MYC, BCL2, and BCL6 rearrangements based on the current WHO classification. The study group was further compared to 157 cases of MYC/BCL2 double hit lymphoma and 13 cases of MYC/BCL6 double hit lymphoma that have been reported previously [18,19,21] ( Table S1). The overall survival (overall survival) of patients with triple hit lymphoma was also further compared with a group (n = 467) of patients with diffuse large B-cell lymphoma without MYC rearrangement.…”
Section: Case Selectionmentioning
confidence: 99%
“…Multiple retrospective studies have shown that patients with double hit lymphoma usually have an aggressive clinical course and very poor outcome [15][16][17][18][19][20][21][22][23][24]. Extranodal disease, a high serum lactate dehydrogenase level, bone marrow and central nervous system involvement and a higher international prognostic index score are frequent in double hit lymphoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…Positivity for MYC, BCL2, and P53 expression was defined by using cutoffs of ≥ 40, ≥ 50, and ≥ 50% positive cells, respectively, as reported in previous studies. 19,21,23,31,32 Flow cytometric immunophenotypic analysis was performed using 8-color flow cytometry. A FACScanto II or FACSCalibur cytometer (Becton-Dickinson Biosciences, San Jose, CA, USA) was used for analysis as described previously.…”
Section: Immunophenotypingmentioning
confidence: 99%
“…Previous studies have shown that patients with diffuse large B-cell lymphoma with MYC-R or MYC/BCL2 double hit have clinically aggressive disease and a poorer prognosis. 6,[10][11][12][13][14][15][16][17][18][19][20][21] Recent studies using immunohistochemical analysis have identified a subset of diffuse large B-cell lymphoma cases that express MYC and BCL2, known as double-positive lymphoma or double expresser lymphoma. Dual expression of MYC and BCL2 (MYC+/BCL2+) has been shown to be associated with a worse prognosis in patients with de novo diffuse large B-cell lymphoma treated with R-CHOP.…”
mentioning
confidence: 99%
“…DA‐EPOCH‐R as first‐line treatment significantly reduced the risk of progression compared with R‐CHOP . Multivariable analyses, however, have not shown that DA‐EPOCH‐R improves OS compared with the standard R‐CHOP . A recent phase II study (NCT01092182) confirmed that DA‐EPOCH‐R produces durable remission in patients with MYC‐rearranged aggressive B‐cell lymphomas with EFS and OS of 71% and 76.7% respectively, at a median follow‐up of 55 months.…”
Section: Introductionmentioning
confidence: 99%